2021
DOI: 10.3390/ijms22073330
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease Pathogenesis: Role of Autophagy and Mitophagy Focusing in Microglia

Abstract: Alzheimer’s disease (AD) is a debilitating neurological disorder, and currently, there is no cure for it. Several pathologic alterations have been described in the brain of AD patients, but the ultimate causative mechanisms of AD are still elusive. The classic hallmarks of AD, including am-yloid plaques (Aβ) and tau tangles (tau), are the most studied features of AD. Unfortunately, all the efforts targeting these pathologies have failed to show the desired efficacy in AD patients so far. Neuroinflammation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 379 publications
(434 reference statements)
0
71
0
9
Order By: Relevance
“…The implication of dysfunctional autophagy in AD pathogenesis and Ab degradation have been investigated but studies mainly focused on neuronal cells (16,17). Few studies have shown that dysfunctional autophagy has significant consequences in AD microglia, including failure to regulate harmful neuroinflammation (17,18). Emerging reports described a role for autophagy-mediated degradation of Ab in AD, yet these studies were performed in cell lines or neonatal microglia, but not in diseased adult AD microglia and underlying mechanisms for dysfunctional autophagy in AD were not offered (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implication of dysfunctional autophagy in AD pathogenesis and Ab degradation have been investigated but studies mainly focused on neuronal cells (16,17). Few studies have shown that dysfunctional autophagy has significant consequences in AD microglia, including failure to regulate harmful neuroinflammation (17,18). Emerging reports described a role for autophagy-mediated degradation of Ab in AD, yet these studies were performed in cell lines or neonatal microglia, but not in diseased adult AD microglia and underlying mechanisms for dysfunctional autophagy in AD were not offered (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Cargo-carrying autophagosomes mature and fuse with lysosomes where degradation of the autophago-lysosome-enclosed material occurs ( 14 ). The implication of dysfunctional autophagy in AD pathogenesis and Aβ degradation have been investigated but studies mainly focused on neuronal cells ( 16 , 17 ). Few studies have shown that dysfunctional autophagy has significant consequences in AD microglia, including failure to regulate harmful neuroinflammation ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The second hallmark is neurofibrillary tangles (NFTs) and hyperphosphorylated tau, which accumulate intracellularly and are typically accompanied by neuronal loss [51]. The tau protein is hyperphosphorylated in AD, which leads to compromised microtubules, thereby disrupting several cellular processes, such as proliferation, differentiation, protein trafficking, and cellular morphology [59,60]. NFTs are abnormal filaments of hyperphosphorylated tau proteins that can be twisted around each other in some stages to form paired helical filaments and accumulate in the neural perikaryal cytoplasm, axons, and dendrites, which causes a loss of cytoskeletal microtubules and tubulin-associated proteins [55].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mediators stimulate transcription factor NF-κB, which is a key regulator in the development of inflammation [120,121]. The NF-κB family of transcription factors is composed of several members such as: NF-κBp50/105, NF-κBp52/100 (RelB), NF-κBp65 (RelA), and NF-κBp75 (c-Rel) with dimers bound by the inhibitory protein IκB.…”
Section: The Role and Regulation Of Nf-κbmentioning
confidence: 99%